2015
DOI: 10.1093/jnci/djv427
|View full text |Cite
|
Sign up to set email alerts
|

Massively Parallel Sequencing-Based Clonality Analysis of Synchronous Endometrioid Endometrial and Ovarian Carcinomas

Abstract: Synchronous early-stage endometrioid endometrial carcinomas (EECs) and endometrioid ovarian carcinomas (EOCs) are associated with a favorable prognosis and have been suggested to represent independent primary tumors rather than metastatic disease. We subjected sporadic synchronous EECs/EOCs from five patients to whole-exome massively parallel sequencing, which revealed that the EEC and EOC of each case displayed strikingly similar repertoires of somatic mutations and gene copy number alterations. Despite the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
202
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 196 publications
(216 citation statements)
references
References 41 publications
13
202
0
1
Order By: Relevance
“…Specifically, we found that 72% of EC cases and 70% of ovarian cancer cases were classified as FIGO stage I (13). Others have confirmed these findings by subjecting cancer tissue from five SEOC cases to whole-exome massively parallel sequencing, demonstrating that the endometrial and ovarian tumor cells displayed strikingly similar repertoires of somatic mutations and gene copy number alterations in all investigated cases (14). These data suggest that in women with SEOC, the endometrium and the ovary represent microenvironmentcompatible sites with preferential dissemination of tumor cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Specifically, we found that 72% of EC cases and 70% of ovarian cancer cases were classified as FIGO stage I (13). Others have confirmed these findings by subjecting cancer tissue from five SEOC cases to whole-exome massively parallel sequencing, demonstrating that the endometrial and ovarian tumor cells displayed strikingly similar repertoires of somatic mutations and gene copy number alterations in all investigated cases (14). These data suggest that in women with SEOC, the endometrium and the ovary represent microenvironmentcompatible sites with preferential dissemination of tumor cells.…”
Section: Discussionsupporting
confidence: 76%
“…the endometrium and the ovary, with a limited capacity for further dissemination (13). Others have confirmed a high rate of monoclonality among SEOC cases (14).…”
mentioning
confidence: 96%
“…Interestingly, we were able to perform exome sequencing analysis in the 3 different areas of the primary tumor and in 1 area of the ovarian mass in 1 case. Our results confirmed a pattern of branched evolution with a significant number of ubiquitous mutations, but also private mutations from different areas of the primary tumor and the ovarian metastasis [13].…”
Section: Next-generation Sequencing Confirms That Ec Follows Branchedsupporting
confidence: 82%
“…Recent preliminary genetic studies suggest a clonal relationship between the two lesions. Given the non-aggressive course seen in many patients, this might mean that malignant tissue arises in the endometrium in these cases and reaches the ovary by transtubal retrograde flow [7]. Immunohistochemically, ovarian ECs express cytokeratin 7 (CK7), paired box 8 (PAX8), estrogen receptors (ERs) and progesterone receptors (PRs).…”
Section: Endometrioid Carcinomamentioning
confidence: 99%